Antihypercholesterolemic and Antioxidant Effects of Blumea balsamifera L. Leaf Extracts to Maintain Luteinizing Hormone Secretion in Rats Induced by High-Cholesterol Diets - I Gede Widhiantara; Anak Agung Ayu Putri Permatasari; I Wayan Rosiana; Putu Angga Wiradana; Luh Putu Widiastini; I Made Jawi (The Indonesian Biomedical Journal, 2021)
BACKGROUND: The discovery of herbal ingredients for antihypercholesterolemic and to improve male reproductive function is very necessary due to high-cholesterol diet factors. Blumea balsamifera leaf extract (BBLE) is known to be able to increase the number and diameter of Leydig cells in rats given high-fat feed. This study was to conducted to determine the levels of total cholesterol, body weight, plasma malondialdehyde (MDA), Superoxide Dismutase (SOD), Luteinizing Hormone (LH) in high-cholesterol-fed male rats provided with BBLE.METHODS: This research utilized a randomized post-test only control group. Ethanol was used to extract the BBLE, which was then evaporated. For 21 days, 16 Wistar rats were given a high-cholesterol diet. To determine the effect of BBLE on the high-cholesterol diet, the samples were divided into two groups (control and BBLE group) on day 22. The treatments lasted 30 days. SOD, plasma MDA, LH, and total cholesterol were measured.RESULTS: The results showed that the SOD and LH parameters were significantly higher in the treatment of BBLE compared to the control group (p<0.05). The parameters of total cholesterol levels, bodyweight, and MDA of rats given BBLE were significantly lower than those of the control group (p<0.05).CONCLUSION: Our findings highlight that BBLE has antihypercholesterolemic and antioxidant effects. The BBLE also has potential to be used as a therapy to maintain male reproductive function because it has a positive effect on the hypothalamic-pituitary axis through increasing LH secretion.KEYWORDS: Malondialdehyde, Superoxide dismutase, Luteinizing hormone, Blumea balsamifera extract, High-cholesterol diet